Upaya Meningkatkan Motivasi Belajar Matematika Siswa SD Melalui Optimasi Game “Moving Twins” - Sa'adah, Miratus; Ningsih, Helen Widiya Kusuma; Ma'rifah, Shokifatul; Saputri, Amalia Mulya; Ilmiyah, Nazril; Avita; Rahayu, Puji (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2024)
Elementary school (SD) students must possess fundamental mathematical abilities. One of them is the capacity to execute numerical calculation procedures. Evidence from the field indicates that the academic performance of primary school kids in mathematics remains at a poor level. This occurs due to the constraints imposed by teachers on pupils' activities at school, leading to a rapid onset of boredom during the learning process. Hence, it is imperative to establish a novel educational environment by leveraging media tools to enhance the enjoyment and dynamism of the learning process. The learning method